ABUSE AUTHORITY BY THE VILLAGE HEAD REGARDING LAND CASH VILLAGE FROM PERSPECTIVE LAW ADMINISTRATION GOVERNMENT - sayekti, lady; Erna Sri Wibawanti; Endang Sulistyaningsih (Fakultas Hukum, Universitas Samudra, 2024)
From the perspective of government administrative law, the protection of Village Treasury Land due to the village head's negligence is a serious violation of law. Village treasury land is a village asset that must be managed well to improve the welfare of village communities and increase village income. However, village treasury land is often converted and sold unilaterally for personal purposes, such as building a residence or housing built on village treasury land. This is a violation of government administrative law because the management of village treasury land is part of public law, which discusses government power in general and village government in particular. The Village Head, as the holder of management power, must manage the Village Treasury Land based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 01 of 2016 concerning Village Asset Management. In managing Village Treasury Land, the Village Head must coordinate with the Village Consultative Body (BPD) to improve the welfare of the Village community and increase Village income. Therefore, the protection of Village Treasury Land due to the Village Head's negligence is a violation of government administrative law that must be followed up.